2002
DOI: 10.1007/bf03165090
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and FISH studies in myelodysplasia, acute myeloid leukemia, chronic lymphocytic leukemia and lymphoma

Abstract: Conventional cytogenetic studies are widely used today to diagnose and manage patients with hematological malignancies. The application of fluorescence in situ hybridization (FISH) with chromosome-specific DNA probes helps to further define molecular subclasses and cytogenetic risk categories for patients with these disorders. Moreover, FISH permits analysis of proliferating (metaphase cells) and non-proliferating (interphase nuclei) cells, and is useful in establishing the percentage of neoplastic cells befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…107002-7 October 2018 • Vol. 23 (10) group, and a positive peak at 1375 cm −1 attributed to glucosamine, which presents in a low concentration in the healthy group compared to the leukemic group. Regarding the carotenoid peaks in plasma, the exploratory analysis by PCA showed that both PC2 and PC4 presented peaks of this component (1004, 1159/1160, and 1520∕1525 cm −1 ), 24,30 and SC2 and SC4 indicated significant differences, indicating the presence of these components in high concentrations in the healthy group, as demonstrated by González-Solís et al, 24 when analyzing Raman spectra of blood in leukemic subjects.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 93%
See 3 more Smart Citations
“…107002-7 October 2018 • Vol. 23 (10) group, and a positive peak at 1375 cm −1 attributed to glucosamine, which presents in a low concentration in the healthy group compared to the leukemic group. Regarding the carotenoid peaks in plasma, the exploratory analysis by PCA showed that both PC2 and PC4 presented peaks of this component (1004, 1159/1160, and 1520∕1525 cm −1 ), 24,30 and SC2 and SC4 indicated significant differences, indicating the presence of these components in high concentrations in the healthy group, as demonstrated by González-Solís et al, 24 when analyzing Raman spectra of blood in leukemic subjects.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 93%
“…38,39 However, the PLS-DA stands out from the PCA-DA because, in addition to the information of the differences between the groups, the variances obtained within each group are also recognized, and these variances are associated to the groups when modeling the regression curve; [38][39][40] therefore, the PLS-DA leads to better performance in the classification of samples when compared to PCA-DA. 38,39 Compared to the techniques currently available for the diagnosis of acute leukemias based on cytomorphology and immunophenotyping, [9][10][11]13,14 RS model presented accuracy (97.1%) close to phenotyping (94% 13 ) and sensitivity and specificity (95.7% and 98.0%) close or overmatch the flow cytometry technique (97% and 88% 14 ), despite the difficulty in obtaining the sensitivity and specificity reference values for the standard diagnostic techniques of myelogram and phenotyping. Thus, Raman-based analysis could significantly differentiate between healthy and leukemic individuals based on differences in the spectral pattern related to the chemical composition (amino acids and carotenoids) of the blood plasma, and cellularity (red and white cells) and chemical composition (proteins) in the whole blood using a small volume of peripheral blood.…”
Section: Discriminant Analysis (Pls-da and Pca-da)mentioning
confidence: 97%
See 2 more Smart Citations
“…In the future, these discoveries may lead to targeted chemotherapy, such as the use of tyrosine kinase inhibitors to target the ectopic expression of receptor tyrosine kinase fibroblast growth factor receptor 3 associated with the t(4;14) translocation (335). Since FISH is a very sensitive technique for the detection of chromosome abnormalities, it is widely used both for diagnosis and for follow-up of MRD post chemotherapy and bone marrow transplant (336)(337)(338)(339).…”
Section: Cytogenetic Analysismentioning
confidence: 99%